2nd price for Best Cypriot Short Film, International Short Film Festival of Cyprus 2025 - Stylianou-Lambert, Theopisti (My University, 2026)
My film "The Archive of Grigoris Antoniou" received the 2nd price for Best Cypriot Short Film, International Short Film Festival of Cyprus 2025 More information here: https://www.isffc.com.cy/2025-edition
Keywords: Arts and entertainment